Judgment Consensus and Auditor Experience: An Examination of Organizational Relations. - Meixner, Wilda F.; Welker, Robert B. (The Accounting Review, 1988)
Previous studies examining internal accounting control judgments have found an inconclusive association between auditor consensus and auditor experience. The present study suggests that an association between judgment consensus and situational experience may be confounded because of the tenure of an auditor with the same audit staff group and/or superior. The adaptive behavior in an organizational relation suggests that judgment consensus among subordinates should increase (i.e., become more congruent) as the subordinate has greater interaction with the audit staff group and/or superior. As support for these expectations, an experiment was conducted using auditors of a state auditor's office. The results indicate that consensus among staff auditors increased as the length of time that staff auditors had been associated with the same audit manager increased, but did not increase based on the length of time that the auditors had been with the state auditor's office.